Diagnóstico Del Aprendizaje Electrónico Móvil (Podcast) Para La Comprensión Auditiva Del Inglés - López, Edison Renato Ruiz; Amaguaya, Patricia Pilar Moyota (European Scientific Journal, ESJ, 2018)
The objective of this research was to evaluate the listening comprehension of the English language through the Mobile electronic Learning (Podcast). A diagnosis was applied to teachers who teach the English language in the Pedro Vicente Maldonado Educational unit of the city of Riobamba. To this end, we analyzed the methodological principles that guide the use of podcast as a didactic tool in the teaching of the English language with emphasis on the dexterity of listening. For the podcast application, multimedia resources were used on mobile devices; while the evaluation was carried out over an eight-week period. The research is descriptive, so the information was developed in a precise and systematic way. The collection of information was through a survey aimed at teachers, the same one that underwent review and was endorsed by academic peers; the analysis of the data was through descriptive statistics, that is to say that the obtained information was tabulated, interpreted and represented by means statistical tables and graphs. Finally, it was determined that the podcast is useful in listening comprehension in the English language learning process, as it constitutes an entertaining and multifunctional technique for teaching..